Casey’s conundrum, a review of the genus Semanotus Mulsant (Coleoptera: Cerambycidae: Cerambycinae: Callidiini) in North America - Hammond, H. E. James; Williams, Daryl J. (Zootaxa, 2013)
The North American species of Semanotus Mulsant, 1839 are reviewed. Semanotus ligneus (Fabricius, 1787), Semanotus amplus amplus (Casey, 1912) new status, S. amplus basalis (Casey, 1924) new status, Semanotus amplus sequoiae Van Dyke, 1923 new status, Semanotus conformis Casey, 1924 new status, Semanotus terminatus Casey, 1912 new status, Semanotus amethystinus (LeConte, 1853), Semanotus juniperi (Fisher, 1915), and Semanotus litigiosus (Casey, 1891) are recognized as valid. A key to the North American fauna, as well as to Semanotus japonicus Lacordaire, 1869 and Seman-otus australis Giesbert, 1993 is included. A morphometric study was conducted using 37 measured characters from adults of S. litigiosus. Data were examined using stepwise discriminant analysis to determine which characters aid in the diag-nosis of taxa, and their amounts of resolving power using canonical variates analysis. Morphometrics revealed significant sexual dimorphism among taxa and suggested that three taxa were present, however, only two taxa could be reasonably separated using observable characters. Phylogenetic analysis using a hypothetical ancestor as out-group returned a single most parsimonious tree for North American Semanotus.